Pengaruh Gaya Kepemimpinan Tansformational, Authentic, Authoritarian, Transactional terhadap Kinerja Guru Pesantren di Tangerang - Agus Purwanto; Masduki Asbari; Agus Hari Hadi (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2020)
The purpose of the study was to analyze the influence of leadership style transformational, transactional, authentic and authoritarian to the performance of teachers in a Pesantren Aliyah in Tangerang Central Java. Respondents to the study were 70 teachers and data collection methods by distributing electronic questionnaires to respondents. Data analysis in this study uses SEM (Structural Equation Model) of LISREL program version 8.70. The results of the analysis and processing of research data show that the leadership style of transactional and authority positively and significantly influence the teacher's performance while the transformational and authentic leadership style is not a significant impact on teacher performance